Shaping a new South America-EU trade relationship (2004)
Notes ongoing discussions between the European Union and Mercosur especially with regard to market access and agriculture. Reports on the opening of negotiations between the EU and 15 Caribbean countries on an economic partnership agreement.
Keywords: FOREIGN TRADE